Aplicación web para el control de la gestión de las actividades complementarias de los docentes de la Universidad Técnica Estatal de Quevedo - Cevallos Muñoz, Wilmer Estuardo (2015)
The project has been implemented in the administrative area of the State Technical University of Quevedo, to develop a web application to control the management of complementary activities undertaken by teachers of the institution. This application will optimize processes registration and control of these activities will allow the use of information shared and safely, ensuring the availability of highly reliable electronic data repositories, which greatly reduces paper usage amount. To achieve this objective we have used the RAD methodology for its acronym in English (Rapid Application Development). Methodology Rapid Application Development is one of the most agile methodologies used in the medium, supplemented with Model Code First development of systems (First the Code), similarly to define the scope and purpose of the rules applied IEEE830 as a starting point in structuring this project. The technology used in this project is completely updated, based primarily on the use of Visual Studio 2013, using the development tool C#, using an editing environment totally friendly code to create web applications, allowing develop interfaces very functional users and pleasant. The management system based MS SQL Server 2012, the same data that has an excellent architecture and robustness in electronic data processing was used to ensure the security and availability of data. Once developed the web application, check the optimization and process efficiency records and control of the follow teachers of the State Technical University of Quevedo, streamlining management, saving time and money, and protecting the environment by avoiding the inappropriate use stationery.